Examining the Role of Digital Competence, Self-Efficacy, and Parental Support in Enhancing Students’ Performance in Sport Education Programs - Indrayana, Boy; Khairunnisa, Fitri; Yusuf, Muhammad (Indonesian Educational Administration and Leadership Journal (IDEAL), 2025)
Advancements in digital technology have reshaped learning across disciplines, including sport education. Yet, the success of digital integration depends not only on students’ technological skills but also on psychological and social factors such as self-efficacy and parental support. This study examines how digital competence, self-efficacy, parental support, and information evaluation strategies jointly affect students’ learning performance in sport education programs. A quantitative survey was conducted with 304 sport education students from Jambi University, Sriwijaya University, and Medan State University. Data were collected through a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0.9.9. Reliability and validity were tested using composite reliability, AVE, and discriminant validity, while model predictive power was assessed through R² and Q² values. All hypothesized relationships were significant. Parental support had the strongest effect on self-efficacy (β = 0.756, p < 0.001) and digital competence (β = 0.746, p < 0.001), which subsequently enhanced information evaluation and learning outcomes (R² = 0.653; Q² > 0.30). Self-efficacy and digital competence also positively affected information evaluation and academic performance, emphasizing that parental motivation fosters confidence and digital readiness essential for effective sport learning. Students’ success in sport education depends on the synergy between technological proficiency, psychological empowerment, and family engagement. Strengthening digital competence alone is inadequate without developing self-efficacy and parental involvement. Hence, educators and policymakers should promote sport education programs that combine digital literacy, reflective thinking, and family collaboration to cultivate confident, adaptive, and high-performing learners in the digital era.  Keywords: Sport Education; Digital Competence; Self-Efficacy; Parental Support; Students’ Performance; Higher Education